Allergy immunotherapy tablet: Grazax® for the treatment of grass pollen allergy. (January 2011) - Senna, Gian Enrico; Calderon, Moises; Milani, Massimo
Immunotherapy is the only treatment for allergy that alters the natural course of this disease. Sublingual immunotherapy has been developed to make immunotherapy more suitable for allergic patients. In the largest clinical program ever conducted with grass allergen-specific immunotherapy, over 2000 adults and more than 500 children have been exposed to Grazax ® (ALK-Abello A/S, Hoersholm, Denmark). Grazax is an oral lyophilisate tablet (allergy immunotherapy tablet [AIT]) for sublingual administration, containing 75, 000 standardized quality tablet units of allergen extract of grass pollen ( Phleum pratense ). Grazax is indicated for treatment of grass pollen-induced rhinitis and conjunctivitis in adult and pediatric patients. Results from the GT-08 trial (first, second and third treatment years) showed a reduction of 31, 36 and 29%, respectively, in symptom scores and a reduction of 38, 45 and 40% of medication scores, respectively, compared with placebo. Subjects treated with Grazax also had an increased number of well days and a relevant improvement in quality of life. More subjects experienced excellent and complete rhinoconjunctivitis control in comparison with patients treated with symptomatic medications only. Grazax treatment is also associated with a sustained and relevant increase of specific IgG4. This increase is also observed after stopping AIT treatment. The most common adverse events related to Grazax treatment are local reactions, such as oral itch, edema of the mouth, ear pruritus, throat irritation and sneezing. Clinical efficacy of Grazax is observed also after 1 and 2 years of follow-up after stopping the AIT treatment. Grazax is efficacious and safe for treatment of grass-pollen rhinoconjunctivitis in both adults and children. Grazax is the first AIT showing a disease-modifying effect on grass pollen-induced allergic rhinoconjuctivitis.